The signal sequence suffices to direct export of outer membrane protein OmpA of Escherichia coli K-12. - Freudl, R (1987)
We studied whether information required for export is present within the mature form of the Escherichia coli 325-residue outer membrane protein OmpA. We had previously analyzed overlapping internal deletions in the ompA gene, and the results allowed us to conclude that if such information exists it must be present repeatedly within the membrane part of the protein encompassing amino acid residues 1 to 177 (R. Freudl, H. Schwarz, M. Klose, N. R. Movva, and U. Henning, EMBO J. 4:3593-3598, 1985). A deletion which removed the codons for amino acid residues 1 to 229 of the OmpA protein was constructed. In this construct the signal sequence was fused to the periplasmic part of the protein. The resulting protein, designated Pro-OmpA delta 1-229, was processed, and the mature 95-residue protein accumulated in the periplasm. Hence, information required for export does not exist within the OmpA protein.